(untitled) (CIPEEX, 2025)
With professional activity occupying a significant part of people’s daily lives, Quality of Work Life (QWL) is fundamental, and healthy and welcoming working environments are necessary for the performance of activities. QWL contributes to the well-being and effective performance of civil servants, who act directly in the implementation of policies and management of public affairs, and their engagement at work is essential to ensure administrative efficiency, the continuous improvement of services and the maintenance of a positive image of the government in society. With this in mind, the aim is to investigate and analyze the determinants that influence the quality of life of civil servants in the workplace. The methodological strategy adopted consisted of a narrative literature review with a qualitative approach. The bibliographic research was carried out using descriptors such as "Quality of life", "Quality of work life" and "public server" in online journals, including Web of Science, PubMed and the Virtual Health Library (VHL). The selection criteria for the articles were predefined, covering the years 2019 to 2024, free access and full text available. Articles with no relevance to the topic of QWL for civil servants were excluded, resulting in the selection of seven articles that best met the established criteria. After analysis, it was observed that QWL encompasses various interpretations and approaches, mainly focused on satisfying the needs of an institution’s employees. Its aim is to promote greater engagement, prevent burnout and improve the physical, mental and emotional well-being of workers, thus helping to improve organizational results. Individuals who experience high levels of QWL tend to perform their duties more productively, which directly benefits the efficiency of the public services offered to citizens. QWL promotes a positive perception of the work environment among employees, resulting in greater satisfaction and well-being. It should be noted that factors such as a suitable physical environment, a balanced workload, positive interpersonal relationships, opportunities for professional development, fair compensation, autonomy in decision-making, health and safety at work are essential to guaranteeing the quality of life of civil servants in the workplace. It should be noted that a low QWL can contribute to the emergence of health problems such as occupational stress, burnout, as well as mental and behavioral disorders. It is therefore essential to determine the quality of working life and levels of job satisfaction, adopting effective measures to improve them, with a view not only to raising the quality of workers, but also the effectiveness of public services.